The adoption of electronic bills of lading in the shipping industry - Lim, Megan Zhi Yan (Nanyang Technological University, 2023)
This project aims to act as an advocate to speed up digitisation in the shipping industry and a call to action so other sectors of the shipping industry follow suit in adopting electronic Bills of Ladings (eBLs) in their trade.